(untitled) (Research, Society and Development, 2020)
In street cocaine production for retail trade, in addition to the active ingredient, other substances are commonly added. The other substances presence, known as adulterants, becomes an additional aggravating factor for user´s health. This work aimed to evaluate qualitatively the cocaine seized by civil police of PI state. For this, 100 cocaine samples seized between the years 2017 and 2018 were used. The GC-MS analyzes identified, mainly, caffeine, phenacetin and levamisole in 58%, 48% and 30% of the samples, respectively. Only 9% the samples did not have adulterants. These adulterants can change cocaine intoxication signs and symptoms since the increase in the power of addiction to the hematological disorders. Finally, is possible to conclude the cocaine seized in the PI does not have a high purity degree and that due the toxicological profile of its main adulterants, these substances identification is a data of great relevance since it helps in understanding of your market and the real risk to user´s health.